“New medical tasks in the new Russia” (1924): The vision of ‘ethnic pathology’ and scientific medicine of Max Kuczynski in the years prior to his emigration to Peru - Knipper, Michael (2005)
Based on an article published originally in 1924, this text offers an approximation to the scientific works and concepts of Maxime Kuczynski-Godard in the years prior to 1933 and his forced emigration from Germany to Peru. The title of the article was “New medical tasks in the new Russia”, and was based on Kuczynski’s experiences made during his time as guest professor at Omsk's Siberian Medical Institute, and his first medical-geographic expedition to the Kyrgyz steppe in Central Asia between 1923 and 1924. In view of the situation in Russia in the post-revolutionary period, the then professor of pathology at the University of Berlin, relates in this article his personal vision of scientific medicine. As a key concept, Kuczynski introduces the notion of ‘cultural’ or ‘ethnic pathology’ as a comprehensive scientific approach that combines theories and methods of natural, social and cultural sciences. The translation of the original article is framed by an introduction and some final notes to provide additional information on the biographic, scientific and historical context.